Comprehending the pharmacological mechanism of marine phenolic acids in bladder cancer therapy against matrix metalloproteinase 9 protein by integrated network pharmacology and in-silico approaches - Roney, Miah; Uddin, Md. Nazim; Mohd Fadhlizil Fasihi, Mohd Aluwi (Elsevier Ltd, 2024)
Bladder cancer (BC) is the 10th most common tumour with a high incidence and recurrence rate worldwide; however, the current therapies present limitations as, regularly, not all patients benefit from treatment. Therefore, the search for new, active marine phenolic acids with anti-tumour properties is imperative. In this study, we subjected marine phenolic acids to in silico investigations such as network pharmacology, molecular docking, and molecular dynamics simulation (MD) to identify a plausible pathway and the lead compound that inhibits BC. According to the network pharmacology analysis, eight hub genes (PLAU, MMP2, ITGB3, MAPK1, PTPN11, ESR1, TLR4, MMP9) were found and linked to the enrichment of hsa05205: proteoglycans in cancer, and four hub genes (MMP1, MMP2, MAPK1, MMP9) were involved in the enrichment of hsa05219: BC. Subsequently, molecular docking studies showed that the marine phenolic acids exhibit a strong binding affinity for the target protein, matrix metalloproteinase-9 (MPP9). Among these 14 marine phenolic acids, chicoric acid showed the highest binding affinity of −67.1445 kcal/mol and formed hydrogen bonds with the residues of Ala189, Gln227, Leu188, His226, Ala242, Arg249, Ala191, and Gly186 in the active site of the MPP9 protein. Then, molecular dynamics simulation revealed that chicoric acid formed a stable protein-ligand complex with RMSD and RMSF values of 0.72 nm and 0.53 nm, respectively. Furthermore, the PCA method was employed to understand the dynamical behaviour in the conformational space of MPP9 protein bound to chicoric acid, and the results showed the good conformational space behaviour of MPP9 protein. Moreover, chicoric acid showed a free binding energy value of −32.62 kcal/mol, which indicated it could be a BC inhibitor. Overall, chicoric acid demonstrated potential anti-BC activity through MPP9 protein inhibition.